2018
DOI: 10.31486/toj.17.0062
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Neuro-Oncology Imaging Techniques

Abstract: Background: Central nervous system (CNS) tumors are a rare but devastating malignancy, often robbing patients of the basic quality of life. Despite advances in our understanding of the CNS tumor disease processes, the prognosis for patients with CNS tumors remains poor. Better characterization and diagnostic and monitoring approaches are necessary to assist in diagnosis and treatment of CNS tumors. One important tool in the neuro-oncology armamentarium is the use of advanced imaging techniques. Methods: We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Readers are referred to excellent review articles about these methods with specific applications to neuro-oncology [ 21 , 82 , 83 ]. In brief, analysis of diffusion MR imaging data provides several parameters such as apparent diffusion coefficient (ADC), mean diffusivity (MD), fractional anisotropy (FA), coefficient of linear (CL), planar (CP) and spherical (CS) anisotropies.…”
Section: Role Of Physiologic Mr and Pet Imaging In The Assessment Of Treatment Response To Immunotherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers are referred to excellent review articles about these methods with specific applications to neuro-oncology [ 21 , 82 , 83 ]. In brief, analysis of diffusion MR imaging data provides several parameters such as apparent diffusion coefficient (ADC), mean diffusivity (MD), fractional anisotropy (FA), coefficient of linear (CL), planar (CP) and spherical (CS) anisotropies.…”
Section: Role Of Physiologic Mr and Pet Imaging In The Assessment Of Treatment Response To Immunotherapiesmentioning
confidence: 99%
“…Since immunotherapies can result in delayed responses, imaging methods can prevent responsive patients from discontinuing a possibly beneficial treatment and similarly can aid non-responsive patients from continuing a potentially harmful and ineffective treatment. Physiologic imaging methods such as diffusion and perfusion imaging as well as amino acid and reporter gene-based positron emission tomography (PET) provide valuable information about tumor biology and microenvironment [ 19 , 20 , 21 ]. Several studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] have reported the potential of these imaging techniques in the evaluation of treatment response to CCRT and antiangiogenic therapies in GBM patients, suggesting that these techniques can also aid in assessing treatment response to immunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…In the event of a brain tumor, clinical manifestations should prompt neuroimaging [28]. The best diagnostic tool to evaluate CNS neoplastic lesions is represented by MRI, which has largely replaced computed tomography (CT), although the latter could still be used in patients with contraindications to MRI or as a quick screening modality [29,30]. In general, in the case of brain tumors surgical resection is the first step when possible and only then radiation therapy follows with or without combined chemotherapy [31].…”
Section: Diagnostic Imaging and Nuclear Medicine In Brain Tumorsmentioning
confidence: 99%
“…Advanced MRI and PET imaging techniques are increasingly gaining the interest of not only researchers but also clinicians, as they have the ability to assist in the identification of biomarkers with the above mentioned ideal characteristics. 34,338 However, key to the identification of neuroimaging biomarkers, which provide robust metrics for patient stratification and for the prognostic evaluation of treatment response, is the standardisation of image acquisition, processing and analysis protocols. 34,338 The has emerged only in the last decade to address the need for better approaches to comprehensively characterise heterogeneous tumours, such as brain, breast, head and neck, and prostate cancers.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…34,338 However, key to the identification of neuroimaging biomarkers, which provide robust metrics for patient stratification and for the prognostic evaluation of treatment response, is the standardisation of image acquisition, processing and analysis protocols. 34,338 The has emerged only in the last decade to address the need for better approaches to comprehensively characterise heterogeneous tumours, such as brain, breast, head and neck, and prostate cancers. 339 Radiomics has the potential to push the current clinical limits of the prognostic ability of radiological datasets, thereby becoming a powerful tool to support clinical decision-making in the era of personalised medicine.…”
Section: Future Research Directionsmentioning
confidence: 99%